Letter from a teacher: A plea for school-university partners to rethink educator burnout and attrition through an ethic of care - Sally Valentino Drew; Kate Atwood Heyboer; Betsy J. Paddock; William Michael McLachlan; Joan Nicoll-Senft (PDS Partners)
Purpose – Guided by several of the 9 essentials of what it means to be a PDS (NAPDS, 2021), authors share a plea to rethink the teacher burnout-attrition-staffing crisis with a call toward a moral imperative of recentering an ethic of care. Many schools are operating under anti-care practices which directly undermine teacher wellness in part due to secondary traumatic stress, rising workload demands and intensive student needs. Design/methodology/approach – Reflecting a compilation of teacher voices, including participants from three research studies and the collective decades-worth experience of educator scholars, this paper presents a synthesis of educator burnout and the role of educator wellness within trauma-informed social emotional learning initiatives. Findings – The practical model of educator resilience offers a potential solution to burnout and attrition by prioritizing care for teachers individually and collectively prior to addressing care for students. Originality/value – The model articulates educator resilience as the motivational force of life within a school community focused on an ethic of care that drives the collective and individuals within the collective to be their best. This aligns with foundation principles of PDS schools and Goodlad and colleagues’ decades-old call to foreground the moral dimensions of teaching in school reform (1990).